Strictly Mining Boardroom: Management Insights from Inside the Resources Sector - Trench, Allan (Major Street Press, 2012)
Strictly (Mining) Boardroom is a mix of boardroom practice, resource sector management and investment observations and discussion, written in Trench’s trademark dry humorous style. Underpinning each theme is an in-depth understanding of the strategic issues and choices being faced by mining companies today. All these ingredients blended together provide for an insightful analysis and greater understanding of Australias mining sector. It takes unique skills to lead a resources company. When you understand what goes on in the boardroom, you better understand the company you are working for or investing in.